BRIEF BIOGRAPHY AND LITERARY CAREER OF JESSE STUART - Pirjanova Mohira Rustam qizi (Western European Studies, 2025)
The purpose of this study was to analayze the biography and literary career.Throughout his literary career, Stuart published over 30 books, including novels, short stories, poetry, and memoirs. His work often dealt with themes of rural life, community, hardship, and the complexities of human relationships in a changing world. Some of his bestknown works include Taps for Private Tussie (1943), The Wolfpen Poems (1951), and The Passing of the Wood (1953). While his works were lauded for their authentic portrayal of Appalachian life, they were also criticized for their sentimentalism and idealization of the region's rural lifestyle.Stuart’s career spanned several decades, during which he received various awards for his literary contributions, including recognition from the National Institute of Arts and Letters. Despite the mixed critical reception, Stuart's work has had a lasting impact on Appalachian literature, highlighting the social and cultural struggles of the region. His commitment to education, culture, and regional identity remains central to his legacy
Keywords: Career; biography; story; novelist